ECONOMICAL EFFECTS OF DIFFERENT PLOWING SYSTEMS FOR PLANTING TWO TYPES OF WHEAT UNDER RAINFED AGRICULTURE CONDITIONS - Yassen H. AL-Tahan (Mesopotamia Journal of Agriculture)
This study was carried out in two sites during agriculture season(2005-2006). The first was at the fields of agriculture and forestry college / University of Mosul. The second one was in Talkaif district , Al-nawaran region (30 km north of Mosul). The aim of study was to compare costs and net revenues of four different tillage systems (mold board plow +harrowing , chisel plow +harrowing , offset disk and no tillage ) for two types of wheat ( large grain and small grain wheat ). Randomized complete blocks were designed by using split plot design with three replications. Means of values were compared according to Duncans multiple ranges test. The results were summarized as follows: No tillage system recorded smallest value of costs in both sites and their average, while the( mold board plow + harrowing) system significantly surpassed in net revenue for Al- nawaran site and the average of both sites . Small grain wheat recorded lowest value of costs and significantly surpassed in net revenue in both sites and their average . Al-nawaran site significantly surpassed in net revenue. The interaction of Al-nawaran site with small grain wheat for all tillage systems and that of college site with small grain wheat for all tillage systems recorded smallest value of grain wheat costs . The interaction of Al-nawaran site with both types of grain wheat by using no tillage system and the college site with both types of grain wheat by using no tillage system recorded smallest value of tillage systems costs .The interaction of Al-nawaran site with small grain wheat by using (mold board plow +harrowing) system recorded highest value of net revenue .